2020
DOI: 10.3390/vetsci7040159
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Diagnostic Approach of Common Virus Diseases in Adult Honeybees

Abstract: Veterinarians are educated in prevention, diagnosis and treatment of diseases in various vertebrate species. As they are familiar with multifactorial health problems in single animals as well as in herd health management, their knowledge and skills can be beneficial for the beekeepers and honeybee health. However, in education and in practice, honeybees are not a common species for most veterinarians and the typical veterinary diagnostic methods such as blood sampling or auscultation are not applicable to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
7
0
3
Order By: Relevance
“…As part of the governmental support of beekeeping in Germany, beekeepers can send a sample of honey bees from colonies that unexpectedly decline in workforce for pesticide residue and pathogen testing to help determine the cause of decline. We have retrospectively re-analysed RNA extracts of 2013, 2019 and 2020 samples for DWV-A and DWV-B using a TaqMan-based qPCR assay, exactly as described in Dittes et al (2020) . We combine 2019 and 2020 samples for ease of interpretation of temporal trends in genotype prevalence.…”
Section: Methodsmentioning
confidence: 99%
“…As part of the governmental support of beekeeping in Germany, beekeepers can send a sample of honey bees from colonies that unexpectedly decline in workforce for pesticide residue and pathogen testing to help determine the cause of decline. We have retrospectively re-analysed RNA extracts of 2013, 2019 and 2020 samples for DWV-A and DWV-B using a TaqMan-based qPCR assay, exactly as described in Dittes et al (2020) . We combine 2019 and 2020 samples for ease of interpretation of temporal trends in genotype prevalence.…”
Section: Methodsmentioning
confidence: 99%
“…Amebiasis is transmitted when a bee ingests M. mellificae cysts that have been eliminated with the feces of an infected bee. The relatively few studies carried out report that the infection is associated with diarrhea, abdomen swelling, lethargy, and death [ 238 , 239 , 240 ]. It has been reported that the presence of M. mellificae in honeybees correlates with Nosema spp.…”
Section: Description Of Main Bee Pathogens and Molecular Methods For ...mentioning
confidence: 99%
“…infections [ 241 , 242 ]. Until now, diagnostics has been carried out by microscopic observation of Malpighian tubes [ 240 ]. Recently, however, a qPCR diagnostic assay with high specificity and sensitivity has been developed based on the 18S rRNA gene sequence as a target [ 243 ].…”
Section: Description Of Main Bee Pathogens and Molecular Methods For ...mentioning
confidence: 99%
“…Vervielfältigung nur mit Zustimmung des Verlages. von Bedeutung [18]. Grund für die Einsendung von Proben war für die Imkernden primär "Totenfall" (n = 89) oder das "Eingehen des Volks" (n = 76), in selteneren Fällen wurden im Vorbericht konkrete Symptome genannt, z.…”
Section: Teil 2 Der Studieunclassified
“…330 Bienen bzw. 31 g einem Volumen von rund 100 ml entsprechen [18]. Mit diesem Probenumfang lassen sich i. d. R. alle relevanten Laboranalysen durchführen.…”
Section: Diskussionunclassified